Value of Ultrasonography in the Diagnosis of Inguinal Hernia – A Retrospective Study - Maisenbacher, Tanja; Kratzer, Wolfgang; Formentini, Andrea; Schmidberger, Julian; Kaltenbach, Tanja; Henne-Bruns, Doris; Graeter, Tilmann; Hillenbrand, Andreas (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The diagnosis of an inguinal hernia is usually made clinically. Precise imaging appears to be necessary when the clinical examination is inconclusive. The aim of this study was to determine the diagnostic value of ultrasonography for inguinal hernias and whether it influences the decision for or against surgery.Materials and Methods This study was a single-center retrospective study carried out from January 2012 to December 2016. All 326 patients had undergone ultrasound scanning of the groin as part of the diagnostic workup. Besides surgical findings being the gold standard, follow-up data and alternative ultrasound diagnoses were considered as references, allowing us to assess the accuracy of negative ultrasound findings as well.Results The findings on ultrasonography were positive in 248 patients and negative in 78 patients. In addition to 201 operated patients, we were able to validate a further 40 patients by means of a questionnaire and the alternative ultrasound diagnoses. The correlation with all three references resulted in a sensitivity of 97 %, a specificity of 77 %, a positive predictive value of 95 %, and a negative predictive value of 87 %.Conclusion Ultrasonography is an accurate method for evaluating inguinal hernias. High sensitivity makes it particularly suitable for ruling out an inguinal hernia when the findings are negative. An ultrasound scan carried out in addition to clinical examination can therefore help to determine the right indication for surgical intervention.
Keywords: ultrasonography; inguinal hernia; diagnostics; retrospective study